Is azathioprine necessary in renal transplantation? - Sheriff, M.H.R.; Yayha, T.; Lee, H.A. (Elsevier, 1978)
Abstract In renal-transplant patients in whom azathioprine therapy was withdrawn early because of bone-marrow suppression no rebound graft rejection was noted. Any subsequent rejection episodes were satisfactorily treated with methylprednisolone pulse therapy. Of 15 patients in whom azathioprine was stopped electively after at least 2 years, only 1 had a subsequent cellular rejection. It is concluded that azathioprine may not have a major role in the immunosuppressive management of renal-transplant patients. If azathioprine has to be stopped there seems to be no good indication for restarting it.
The Lancet: 1978; 311(8056); 118-120